ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PTPN IV UNIT KEBUN TEH SIDAMANIK PROVINSI SUMATERA UTARA - Sri Rahayu; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at PT. Perkebunan Nusantara IV Sidamanik Tea Plantation Unit, North Sumatra Province, with the problem in the research, namely the decline in the company's ability to obtain profitability. The purpose of this study was to knowing and analyze the management of working capital in increasing company profitability. The types and sources of data used are secondary data originating from the financial statements of PT. Perkebunan Nusantara IV Sidamanik Tea Plantation Unit for the period 2017-2021. The data collection technique used the method of financial statement documentation, in this research using the type of quantitative descriptive data, while the data analysis technique used by the author in this study was ratio analysis. The ratios used in this study include activity ratios (total asset turnover and working capital turnover), liquidity ratios (current ratio, quick ratio, and current ratio) and profitability ratios (net profit margin, return on assets, and return on equity). . The results showed the results of the calculation of the ratio at PT. Perkebunan Nusantara IV Sidamanik Tea Plantation Unit, namely the activity ratio shows that the total asset turnover and working capital turnover fluctuated. The liquidity ratio in the current ratio and quick ratio has increased and the cash ratio has fluctuated. The profitability ratio shows that the net profit margin, return on assets, and return on equity have fluctuated during the last five years. Keywords: Working capital, Activity ratio, Likuidity ratio, Profitability ratio